Communal-Digital Model for Housekeeping Efficiency: A Participatory Action Research in a Resource-Constrained Frontier Region - Milyardo, Boiris; Zakharia, Friend; Leki, Erwin Rivaldo (Journal of Tourism Sustainability, 2026)
The persistent failure of standardized digital management platforms to resolve operational rifts in frontier tourism destinations stems from a fundamental misalignment between technocentric design and regional infrastructural fragilities. This study evaluates a Communal-Digital Model designed to bridge these gaps by anchoring frugal digital tools within indigenous collectivist ethics. Employing a ten-week Participatory Action Research design at a mid-scale hotel in Indonesia, the research involved 15 housekeeping personnel using messaging platforms and offline spreadsheets analyzed via reflexive thematic analysis and quantitative performance metrics. Implementation resulted in a 44.4% reduction in room turnaround duration and an 80% decrease in inventory auditing discrepancies, while autonomous staff engagement increased from 30% to 85%. These findings validate the conceptual framework of digital communalism, proving that traditional social capital drives technological transformation in non-Western, resource-scarce contexts.